Internationalization of social work: contributions to the debate of the profession - Schmitt, Adriana Regina Vettorazzi; Sarmento, Helder Boska de Moraes (Argumentum, 2023)
The internationalization of Social Work, today, is a condition that is imposed in the construction of knowledge. And this requires deepening its theoretical perspectives, political and historical direction. In an effort to contribute to this debate, it is assumed that it is necessary to understand what we call here the educational-academic dimension of this process of internationalization of the profession, whose objectives in this article are: a) to present the debate on the internationalization of higher education through theoretical-epistemological reflections by national and international authors beyond Social Work; b) highlight the relevance of collaborative knowledge networks that act as internationalization mechanisms; c) discuss the presence of an internationalization process throughout the history of the profession. The research methodology is constituted in an exploratory phase, based on the bibliographical survey and its respective revision, for the knowledge of the main international authors that deal with the issue. It is indicated in this article that national and Latin American research has critically reconstructed the paths of this forced and dominating internationalization of the profession, however, with globalization these relationships needed to be reassessed, as this implies its future as a profession, academic discipline and area of ​​study.